2019
DOI: 10.1002/alr.22305
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of sinonasal inverted papilloma resection by surgical approach: an updated systematic review and meta‐analysis

Abstract: BackgroundSelecting the optimal surgical approach for resection of sinonasal inverted papilloma (SIP) remains a challenge, with endoscopic, external, and combined approaches being utilized. This systematic review was conducted as an update to a 2006 systematic review to determine the preferred surgical approach for tumor control.MethodsThe study protocol was developed a priori following the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) process. Data were collected and outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 95 publications
3
44
2
1
Order By: Relevance
“…A recent meta-analysis showed that the recurrence rate after endoscopic surgery is lower than it was after external surgery before the introduction of endoscopic approaches. 10 In addition, the newly introduced surgical techniques of EMLP and prelacrimal approach have enabled further extension of the indications for endoscopic surgery for IP. The EMLP approach has made it possible to approach the lateral wall of the frontal sinus, and the prelacrimal approach has enabled approaching the anterior and medial walls of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis showed that the recurrence rate after endoscopic surgery is lower than it was after external surgery before the introduction of endoscopic approaches. 10 In addition, the newly introduced surgical techniques of EMLP and prelacrimal approach have enabled further extension of the indications for endoscopic surgery for IP. The EMLP approach has made it possible to approach the lateral wall of the frontal sinus, and the prelacrimal approach has enabled approaching the anterior and medial walls of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…47 An endoscopic approach reportedly achieves equal or superior recurrence rates compared with a conventional external approach. 810 However, in some cases, it is impossible to achieve complete resection endoscopically and an external incision is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Inverting papilloma (IP) is a challenging condition to manage in the sinonasal cavity. A recent literature review has shown that the best surgical approach to the management of IP is endoscopic [1]. However, the challenge remains on how to best surveillance these patients postoperatively, especially if the recurrence converts to malignant transformation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge remains on how to best surveillance these patients postoperatively, especially if the recurrence converts to malignant transformation. To our knowledge, the most up to date IP recurrence rate is 13.72% with a malignant transformation potential of 7.6% [1][2][3]. Given that the recurrence and malignant transformation can happen more than 8 years after the preliminary surgery, followup of 3 years or greater is recommended [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation